2016
DOI: 10.1021/acs.jcim.6b00305
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Protein Stability by Comparative Molecular Dynamics Simulations of Homologous Hyperthermophilic, Mesophilic, and Psychrophilic Proteins

Abstract: In the present studies, we analyzed the influence of temperature on the stability and dynamics of the α subunit of tryptophan synthase (TRPS) from hyperthermophilic, mesophilic, and psychrophilic homologues at different temperatures by molecular dynamics simulations. Employing different indicators such as root-mean-square deviations, root-mean-square fluctuations, principal component analysis, and free energy landscapes, this study manifests the diverse behavior of these homologues with changes in temperature.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 49 publications
0
24
0
Order By: Relevance
“…1C). To this end, we monitored structural quantities such as RMSF and RMSD to assess protein stability and deviation from the reference IDS WT crystal structure (Khan et al, 2016;Demydchuk et al, 2017;Dong et al, 2018). The larger RMSF and RMSD values for IDS W337X (Fig.…”
Section: Simulationsmentioning
confidence: 99%
“…1C). To this end, we monitored structural quantities such as RMSF and RMSD to assess protein stability and deviation from the reference IDS WT crystal structure (Khan et al, 2016;Demydchuk et al, 2017;Dong et al, 2018). The larger RMSF and RMSD values for IDS W337X (Fig.…”
Section: Simulationsmentioning
confidence: 99%
“…Previous studies have suggested that the activity of enzymes is directly correlated with the flexibility of their active site, connecting rigidity with loss of function in most cases (Khan et al, 2016;Rashin et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that the activity of enzymes is directly correlated with the flexibility of their active site, connecting rigidity with loss of function in most cases(Khan et al, 2016;Rashin et al, 2010). Ligand interactions with its target site increases side-chain rearrangements and may also contribute to conformational changes otherwise bound to enzymatic processes.…”
mentioning
confidence: 99%
“…The loop6 and loop2 has been reported important for catalytic activity of α-subunit of TRPS that facilitate ligand retention as well as its interaction inside the binding pocket (Khan, Farooq, & Kurnikova, 2016). The RMSF analysis of benzamide inhibitor protein complex showed major fluctuations in loop6 region that help in orientation of active site in order to retain ligand inside binding pocket as depicted in Figure 6(A).…”
Section: Molecular Dynamic Simulationsmentioning
confidence: 95%